Application of Ethics in Business Latitude (Case Study of Fabric Traders in Medan's MMTC Market) - Ambrosya Friera; Dyamawani Trinovelia Purba; Inda Serfina Tarigan (PT FORMOSA CENDEKIA GLOBAL, 2022)
The purpose of this study is to determine the application of ethics in doing business at the Medan MMTC Market. This research uses qualitative research that produces descriptive data, descriptive research is research that only describes the state of the object or problem, using interviews and direct observation methods. This research was conducted at Pasar Raya MMTC Medan on Jl. Willieam Iskandar, New Memories, Kec. Percut Sei Tuan, Kab. Deli Serdang, in order to obtain an overview of the application of ethics in doing business at Pasar Raya MMTC Medan. Observations and interviews conducted show that traders understand and apply business ethics in trading, where honesty is a very important and relevant principle for business activities, and customer service is a very important aspect in trading where this affects trust and image. business